On the chronology of the copper puls from Shahr al-Jadid (Old Orhei) - Crivenco, Andrei; Nisenboim, Igor (Revista Arheologică, 2026)
The article is devoted to the chronology of the emissions of copper puls of the Golden Horde city of Shahr al-Jadida (Old Orhei), based on the analysis of numismatic material. The study examines the main types of urban copper coinage, their epigraphic and stylistic features, as well as die links. Comparison of the obtained data with the characteristics of the emissions and the stylistic features of the silver dang coinage of Shahr al-Jadida makes it possible to refine the dating of individual series of copper puls. The results of the research expand the possibilities of using this group of coins as reliable chronological markers and contribute to a better understanding of monetary circulation in Shahr al-Jadida during the final period of this Golden Horde city’s existence.